Analysis of thermal and solutal transport in Casson nanofluid flow around a rotating cylinder subject to mixed convection and radiation - Faisal Nazir; Jawad Ahmed; Thabet Abdeljawad; Ali Alshamrani; Khadijah M. Abualnaja; Mohamed Abdelghany Elkotb (Case Studies in Thermal Engineering)
The thermal and solutal transport in a Casson nanofluid flow around a vertically rotating cylinder under mixed convection and nonlinear thermal radiation is investigated in this work. In order to account for thermophoresis and Brownian motion effects, the work ingeniously incorporates the Buongiorno nanofluid model while also taking into account Joule heating, heat source/sink, and magnetic field interactions-a configuration that has not been investigated before. Using proficient numerical solutions with MATLAB's bvp4c solver, we show that the system's momentum increases as the buoyancy ratio and mixed convection parameters increase, and that thermal phenomena intensify as the radiation numbers increase. Further the Nusselt number increases by 19.5 % with thermophoresis and 48.9 % with Biot number. Moreover, Lewis number increases the Sherwood number by 16.3 %, but Brownian motion only increases it by 0.2 %. These findings offer novel perspectives for enhancing thermal control in high-performance applications where nanoparticle-enhanced heat dissipation and fluid stability are critical, such as turbine cooling and biomedical devices.